Idolatry and Representation the Philosophy of Franz Rosenzweig Reconsidered. - Batnitzky, Leora (Princeton : Princeton University Press, 2001)
Although Franz Rosenzweig is arguably the most important Jewish philosopher of the twentieth century, his thought remains little understood. Here, Leora Batnitzky argues that Rosenzweig's redirection of German-Jewish ethical monotheism anticipates and challenges contemporary trends in religious studies, ethics, philosophy, anthropology, theology, and biblical studies. This text, which captures the hermeneutical movement of Rosenzweig's corpus, is the first to consider the full import of the cultural criticism articulated in his writings on the modern meanings of art, language, ethics, and natio.
Book Cover; Title; Copyright; Contents.
Description based on print version record.
Keywords: Philosophy; Rosenzweig, Franz, -- 1886-1929.; Judaism -- Doctrines; Idolatry; Jewish philosophy; PHILOSOPHY / Eastern; Electronic books